Verification of risk scores to predict i.v. immunoglobulin resistance in incomplete Kawasaki disease. Issue 2 (3rd December 2015) - Kanamitsu, Kiichiro; Kakimoto, Hisako; Shimada, Akira; Nakata, Yusei; Ochi, Hiroaki; Watanabe, Hirokazu; Iwasaki, Yuka; Tokorodani, Chiho; Kanazawa, Akane; Maruyama, Hidehiko; Miyazawa, Mari; Nishiuchi, Ritsuo; et al.
Abstract: Background: A recent study indicated the efficacy of the addition of prednisolone to i.v. immunoglobulin (IVIG) as initial treatment in patients with higher risk of IVIG resistance. Several different risk scores for predicting IVIG resistance have been proposed, mainly based on typical Kawasaki disease (KD) patients. We investigated the utility of the risk scores to predict IVIG resistance in incomplete KD. Methods: Clinical records of incomplete KD patients who received a single dose of IVIG between 2005 and 2012 at Kochi Health Sciences Center were retrospectively reviewed. Patients were classified into an IVIG‐responsive group and an IVIG‐resistant group. The Kobayashi, Egami, and Sano risk scores were calculated for each patient and the proportion of high‐risk patients was compared between the two groups for each risk score. Results: For 51 incomplete KD patients, Kobayashi (66.7% vs 47.6%, P = 0.253), Egami (55.6% vs 38.1%, P = 0.274), and Sano (57.1% vs 10.8%, P = 0.068) risk scores identified a higher proportion of high‐risk patients in the IVIG‐resistant group compared with the IVIG‐responsive group, but significant difference was not observed. Sano risk score had the highest OR (6.19; 95%CI: 1.00–38.26). Conclusions: The proportion of patients identified as being at high risk for IVIG resistance using the Kobayashi, Egami, and Sano risk scores, respectively, was not significantly different between the IVIG‐responsive group and the IVIG‐resistant group for incomplete KD. Among the three risk scores, the Sano risk score has the best ability to predict IVIG resistance in incomplete KD.